Sāmoan settlement pattern and star mounds of Manono Island - Sand, Christophe; Baret, David; Bolé, Jacques; Ouetcho, André-John; Sahib, Mohammed (Waka Kuaka, 2018)
The small island of Manono, positioned between Upolu and Savaii in the Samoan Archipelago, is known in oral traditions of West Polynesia as having had an important political role during the immediate pre-Christian period. An archaeological programme carried out between 2012 and 2015 has mainly concentrated on the mapping of parts of the northern half of the island, around Salua Village. This has allowed us to study in detail a portion of the slope as well as the central plateau of Manono, known to preserve a star mound first mapped in the 1960s during the large-scale programme organised under the direction of R.C. Green and J.M. Davidson. Our mapping of the 9ha fortified ridge has identified another 13 star mounds of different shapes and types, representing the largest concentration of this specifically Samoan layout known to date in this part of the archipelago. These are associated with another two structures of distinctively Tongan typology, referred to as sia heu lupe. Initially we present the general settlement pattern of the northern part of Manono Island. This is followed by a review of the main characteristics of the 14 mapped star mounds and data on their chronology. The diversity of size, height and number of arms is addressed, showing significant differences in work expenditure between individual platforms. This variability is best illustrated by the identification of three star mounds that lack central fill and are only recognised as wild pigeon-snaring structures by the presence of raised branches/arms. Finally, the Manono settlement pattern data are positioned in relation to the larger study of the pre-Christian history of Samoa.